Hybrid agency in a boundary-blurring space: the development of an (inter)national legal market in Cabo Verde and Mozambique - Santos, S. (Research handbook on the sociology of legal ethics, 2025)
The development of law firms in Cabo Verde and Mozambique dedicated to corporate law and international investment projects aligns with the rapid expansion of globalized financial markets.1 Portuguese law firms have used different channels and instruments—legal, economic, political, and cultural cooperation—to enter and shape these markets.2 One of the forms used is the training of local practitioners and the establishment of partnerships ensuring a strategy of legal, economic, and political influence that can be described as postmodern colonialism.3 Portuguese firms explore the country’s colonial past in Western and Southern Africa and its colonial legacies, particularly the weight of the Portuguese legal system in forming new independent legal systems, and the unequal circulation of persons, capital,4 and commodities. This chapter aims to study the contemporary development of law firms and legal practice in Cabo Verde and Mozambique and how the internationalization of Portuguese law firms into Portuguese-speaking countries in the African continent creates new challenges to the regulation of the profession,5 namely the definition and the boundaries of legal and illegal practice. The internationalization process6 can potentially impact the development of the local legal market7 and lawyers’ professional and ethical practices. Working in a global law firm8 and across two jurisdictions can challenge ethical behavior and professionalism9 toward the firm, clients, other legal professionals, and society in general.